Exploring Predictors of School Belonging in Senior High School Students - Adinata, Rangga Satria; Hanami, Yuliana (TAZKIYA Journal of Psychology, 2024)
Adolescents spend a lot of time at school because schools are centers of activity for them. Thus, it is normal for students to feel supported, comfortable, and connected to all components of the school. These feelings can make students think of themselves as part of their school or known as school belongings. This research was conducted to explore what factors can affect school belonging and to find the factors that have the most meaningful influence on school belonging for high school students in Indonesia. This research used a qualitative approach with a generic qualitative approach, and consisted of five participants who were 10th and 11th grade high school students attending schools in Bandung. Data analysis uses reflexive thematic analysis. The results of the study revealed that four themes could affect school belonging for students at school, including relationships with school members, adequate learning facilities and infrastructure, students' participation in extracurricular activities, and the match between students' interests and their school majors. On the other hand, it was found that peers were a factor that consistently influenced students' school belongings because it is consistently mentioned by every subject in this study.